PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT. PENDANAAN TEKNOLOGI NUSA DI TANGERANG, BANTEN - Rizsky Afrizal Ramadhan; Sigit Purnomo (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to find out the effect of Reward and Punishment on the performance of PT. Duan Teknologi Nusa employees in Tangerang, Banten. This type of research is a quantitative type of research using descriptive methods. The data collection technique using the questionnaire method, the population in this study was all employees of PT. Duan Teknologi Nusa, namely 64 employees using saturated samples. The data analysis techniques in this study are statistical analysis using validity test, reliability test, classical assumption test, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient determination test, hypothesis test and f hypothesis tests. The results of research on the effect of Reward and Punishment on employee performance at PT. Duan Teknologi Nusa in Tangerang, Banten are shown by the multiple linear regression equation Y = 1.114 + 0.452 X1 + 0.582 X2. This is evidenced by the simultaneous hypothesis test results obtained by the F count values > F table or 93.218 > 3.15 and reinforced by a significance value of 0.000 < 0.05. The results of the coefficient of determination of the Reward (X1) and Punishment (X2) variables test have an effect of 75.3% on the performance of employees at PT. Dana Teknologi Nusa in Tangerang, Banten. Thus H0 was rejected and H3 was accepted. This means that there has been proven to be a significant simultaneous influence between Reward (X1) and Punishment (X2) on employee performance (Y).